Prevalence of Asymptomatic Brucellosis in Children 7 to 12 Years Old - Aghaali, Mohammad; Mohebi, Siamak; Heydari, Hosein (Interdisciplinary Perspectives on Infectious Diseases, 2015)
Background. Brucellosis is one of the most common diseases of humans and animals and its clinical manifestations differ from asymptomatic infection to chronic illness associated with recurrence of symptoms. This study aimed to evaluate the prevalence of brucellosis in asymptomatic children 7 to 12 years old in Kahak, Iran. Methods. In this study, 186 children 7 to 12 years old were evaluated. Demographic data and exposure to the brucellosis agent were recorded and blood samples for the Wright, Coombs, and 2ME tests were collected. All the study subjects were followed up for one year about the appearance of symptoms. Results. The mean age was 10 ± 1.72 years and 51% were boys. Family history was positive for brucellosis in 15% of children. A total of 8 children were brucellosis seropositive and, in subsequent follow-up, 6 of them showed the disease symptoms. Conclusion. This study showed that approximately 4.3% of children in endemic areas can have asymptomatic brucellosis and many of these children may be symptomatic in short term.